Development of safety culture in the construction industry: The leadership and training roles - Misnan, Mohd Saidin; Mohammed, Abdul Hakim; Wan Mahmood, Wan Yusoff; Mahmud, Syamsul Hendra (2008)

(untitled)
The construction industry is unique among industries. The activities of construction often take place outdoor under conditions not condusive for safety and health. Workers in the construction sites have to face constant change in the nature of work, the location of work and the mix of workers. The nature of most accidents at construction recurrent and serious shows that the construction industry is unique. As buildings become higher and larger, the possibility of accidents to occur also increases. However, it is not possible to control all the hazardous activities at a construction site. Factors involved in accidents include human behaviour, different construction sites, the difficulties of work, lack of safety culture, unsafe used of machinery and equipment, and noncompliance with various sets of procedures. Studies show that an accident and injury at the worksite is often the result of workers’ behaviour and safety culture. Safety culture is more related to workers’ safety practices. An efficient safety management system ought to be based on the safety awareness that should become a culture in the construction industry involving all the parties. The efficient safety culture should be shown to the public as a good value business. Leadership is an essential part of the process of management and it is also an integral part of the social structure and culture of the organization. In addition to providing key skills and knowledge, training can be used to motivate and to modify behavior and attitudes. This paper discusses the framework of the development of safety culture in the construction industry through leadership and training roles although known as one of the dangerous industry but will provide a safe working environment thus offering a safe and promising career. Safety culture is an alternative for encouraging competition at any level in order to reduce number of accidents, fatalities and injuries that involves workers and properties.